The Effect of Different Reynolds Number On Solid Sphere Using CFD and Its Verification - Azahar, Mohamad Amirur Rahman; Ishak, Izuan Amin; Sulaiman, Syabillah; Jaat, Norrizam; Zulkifli, Abdul Fathul Hakim; Sukiman, Safra Liyana; Osman, Kahar; Darlis, Nofrizalidris (International Journal of Integrated Engineering, 2023)
Aerodynamic behaviour of an object depends on several factors, namely shape, size and flow conditions. Thus, CFD simulations are an effective engineering tools that allows major contribution to understand the flow conditions around an object. This study aims to analyse the effect of two various shapes of spherical models on aerodynamics behaviour for different Reynolds number between 100,000 â‰¤ Re â‰¤ 800,000. Geometry models are generated using SolidWorks 2017 and numerical solution is analysed using ANSYS CFX. The numerical results are later compared with experimental data collected from wind tunnel. At the end of the study, the nature flow around spherical models of different Reynolds number are visualized. It is discovered that the flow behaviour around the spherical model changes as the Reynolds number increases. This finding is parallel with past researchers. These forecasts should assist engineers enhance the application of aerodynamic and hydrodynamic design.